The relationship between PTSD, hypervigilance and disordered sleep - Van Wyk, Mariza (Department of Psychology, 2015)
Disordered sleep in PTSD constitutes a major component of the presenting symptomatology. However, the literature on PTSD and sleep is characterized by discrepancies across studies, especially due to the fact that some use objective and some use subjective measures of sleep quality. As a result, disordered sleep and its underlying mechanism have been ambiguously characterized in PTSD. Our research focused on the link between PTSD and disordered sleep, using both objective and subjective measures of sleep quality. Specifically, we investigated hypervigilance (one of the three symptom clusters in the PTSD diagnosis) as an underlying mechanism of this link. We also investigated whether hypervigilance affects dream content and themes in individuals with PTSD.